Identity Struggle Perspective in Car-Shaped Shrine in Paluang Temple, Nusa Penida Bali, Indonesia - Dwijendra, Ngakan Ketut Acwin (International Journal of Psychosocial Rehabilitation, 2020)
Car-shaped shrine (pelinggih) in the Paluang Temple Nusa Penida is an altar for worship a symbol of the God manifestation Ida Bhatara Ratu Gede Sakti Ngurah and Hyang Mami or Siwa Durga. The shape of the pelinggih are the VW Beetle and the Jimny Jeep. This is the identity of its existence, so it is viral on social media. This study reveals the socio-architectural phenomenon of this car shrine in the period determined by the Klungkung Kingdom era until in digital media era today. Revealing the process of meaning and actors who capture knowledge behind the car pelinggih identity to be used by cultural discourse. This research uses qualitative methods using descriptive analytics. Data collection with observation and documentation. Determination of informants is done by purposive sampling. Data analysis with poststructuralism approach, power genealogy methodology of Foucault’s, and theory of discourse-power-knowledge relations also from Foucault. The end result, turned on by most of the local and outside communities of Bali, the knowledge hidden in these discourses has moved the community in each era, to reach each other’s purposes, namely as identity contestation, and consumption of identity.